The role of digitalization in harmonizing financial interests and financial behavior - O. V. Onyshko (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
This article examines the impact of digitalization processes on the need for a deeper analysis of financial relations, specifically concerning the formation of financial interests and the financial behavior of their participants. It emphasizes the importance of intensive efforts to realize financial interests at the state, business entities, and household levels, given the global influence on their quantitative and qualitative characteristics, as well as the interdependence and correlation of the categories “interests” and “behavior” as a result of military actions and the use of computer and information technologies. According to the obtained results, in the context of satisfying financial interests and through the appropriate transformation of financial behavior, real opportunities emerge to accumulate the potential of financial relations for solving important problems with the necessary efficiency. It is argued that for understanding modern interconnections in solving behavioral problems, the most significant positions are those corresponding to systemic approaches, as well as adaptive mechanisms closely related to the interests and behavior of economic agents. The behavioral interpretation of financial relations, aimed at achieving consensus and compromises between financial interests and financial behavior, should be based on the integration of traditional and novel approaches within the concept of flexible finance and on the platform of financial-digital tools. In this context, attention is drawn to the use of Agile methodology (Agile Finance), which forms the basis for a new direction in the development of behavioral finance. It is noted that the principles of this methodology, defined in The Agile Finance Manifesto, are aimed at creating a common language and value system that allows partners to align their interests and effectively work as a financial team in conditions of constant change. This makes financial processes flexible, fast, and collaboration-oriented. As a result, there is a clear balancing and harmonization of interests and the real behavior of participants in financial relations, transforming their unity into a crucial system-forming link in the functioning of the modern financial economy at all its levels.